Influence of the constitutive model in the damage distribution of buildings designed with an energy-based method - Donaire-Avila, Jesus; Benavent-Climent, Amadeo; Mollaioli, Fabrizio (Frontiers in Built Environment, 2023)
It is widely accepted in the seismic design of buildings a certain level of damage under moderate or severe seismic actions but preventing the damage concentration in them. Overall, most standards propose heuristic criteria that deal with the damage concentration issue indirectly and not through explicit procedures. On the other hand, the energy-based design methodology proposes an optimum strength distribution for designing the structure of the building aimed at achieving an approximated even distribution of the damage —energy dissipated by plastic deformations— under seismic actions. Different approaches for the optimum strength distribution have been proposed in both the literature and standards. Most of them were formulated from the results obtained in non-linear numeric evaluations of elastic-perfectly plastic (EPP) structures, such the proposed recently by the authors. However, studies on the optimum strength distributions of reinforced concrete (RC) structures are scarce. The present study sheds light on this issue. Accordingly, the structures of four prototype buildings with 3, 6, 9 and 12 stories were designed through an energy-based method by using five approaches for the optimum strength distribution: those proposed by the authors and two others from the literature and standards. Then, different prototypes of the structures arose considering the different approaches for the optimum strength distribution, two soil classes (dense and medium dense) and two ductility levels (low and high). Such prototype structures were subjected to two sets of far-field ground motion records by using three different constitutive models for the shear force-interstory drift relationship: EPP, Clough model and Modified Clough model. The first characterizes the steel structures and the rest are typical for RC structures. A complete analysis was carried out to obtain the distribution of damage for EPP and RC structures, their deviations respect to the “ideal” even distribution of damage and the possible damage concentration on specific stories. RC structures showed higher dispersion for the distribution of damage than EPP structures, although those designed with the optimum strength distributions proposed by the authors showed the lowest values, in the order of those obtained with EPP structures designed with optimum strength distributions proposed in the literature.